Structural polymorphism in self-assembled networks of a triphenylene based macrocycle - Mali, Kunal S.; Schwab, Matthias Georg; Feng, Xinliang; Muellen, Klaus; De Feyter, Steven (Physical Chemistry Chemical Physics, 2013)
Understanding and controlling the structural polymorphism in self-assembled networks of functional molecules merit special attention. In this contribution, we describe the concentration controlled structural evolution in self-assembled monolayers of a large triangular discotic macrocycle at the liquid-solid interface. Scanning tunneling microscopy (STM) reveals that the adlayers formed by an alkoxy substituted cyclo-tris(7,9-triphenylenylene) macrocycle exhibit concentration dependent 2D phase behavior at the 1,2,4-trichlorobenzene/HOPG interface. The self-assembled network evolves from high-density linear packing which is formed at relatively high concentrations to a low-density porous pattern at lower concentrations. A trimeric hexagonal phase exists at intermediate concentrations examined. The transformation of the trimeric hexagonal phase to the linear phase could be monitored by recording time-dependent STM images. The self-assembly behavior is affected significantly by the choice of the organic solvent where an amorphous network is formed along with high-density linear packing at the 1-phenyloctane/HOPG interface. The results presented here provide detailed insight into the polymorphism phenomenon exhibited by an organic semiconductor and furnish general guidelines to control the morphology of thin films of such technologically important materials. This journal is © the Owner Societies 2013.
CRIS-Team Scopus Importer:2023-03-20